Modernity and the Question of Transcendence (Understanding the Fixed and the Variable in Adonis’s Thought) - hhattab, hanane (El Omda in Linguistics and Discourse Analysis, 2022)
This research paper aims at identifying the modernist thought based on the principle of liberation and emancipation from the dominant pattern and imprisonment of the past. In order to establish the idea of openness and transcendence, in which the ideas of the critic Adonis have emerged, attempting to oppose the centralization of heritage, eliminating the Arab model by giving it alternatives consistent with Western modernist thought. On the basis of this study, the question of transcendence and identity, and the fixed and the variable controversy is arised. This is due to the place occupied by the Arab and Islamic heritage in the collective memory